Psycho-fitness parameters in the identification of high-potential archers - Rabiu Muazu, Musa; Zahari, Taha; Anwar, P. P. Abdul Majeed; Mohamad Razali, Abdullah (Springer Singapore, 2019)
This chapter highlights the relationship of psycho-fitness variables towards the recognition of HPA and LPA. The variables, namely hand grip, upper muscle strength, core muscle strength, static balance, vertical jump and athletic coping skills, were shown to be able to provide a reasonable clustering of the archers. Moreover, it was established that the coarse variation of the k-NN model yields the better classification of the HPA and LPA.